Experiments with solar energy - Halacy, D. S. (Daniel Stephen), 1919- (New York, W. W. Norton, 1969)
Instructions for performing experiments which demonstrate many possible uses for presently wasted solar energy.
Includes Index.
Bibliography: p. [141]
Keywords: Solar energy -- Experiments -- Juvenile literature; Solar energy -- Experiments